Effect of Lyophilized Bovine Colostrum on Growth and Survival of Newborn Piglets From Local Breed, in Benin Republic - Agbokounou, Aristide Mahoutin; Ahounou, Gbênagnon Serge; Karim, Issaka Youssao Abdou; Mensah, Guy Apollinaire; Koutinhouin, Bénoît; Hornick, Jean-Luc (European Scientific Journal, ESJ, 2018)
In Benin, the effect of supplementation of newborn piglets from local breed with lyophilized bovine colostrum was evaluated over a 49-d trail on the survival, the growth performances and the absorption of bovine and porcine immunoglobulin G (IgGs). Three groups of 24 piglets, stemming from five sows (Parity 2) belonging to a unique traditional farm, were respectively fed for the first 7 d of life with only sow colostrum (SC group n = 9), shea butter in addition to suckling (SCB group; n = 7) and a mixture of lyophilized bovine colostrum and shea butter in addition to suckling (BCB group; n = 8). Risk of diarrhea was not affected by the treatments, but BCB treatment tended to reduce it (P = 0.09). Diarrheal and healthy piglets had similar average levels of serum porcine IgG at 10 d (13.9 ± 1.6 mg/ml vs 14.7 ± 1.4 mg/ml, P > 0.05). No bovine IgG was detected in the piglets serum at 10 d of age. Serum porcine IgG at 10 d was not affected by the treatments (P > 0.05). However, bovine colostrum improved serum IgG at 49 d (P < 0.05). No significant difference (P > 0.05) was observed between the three groups for body weight and Average Daily Gain (ADG). By contrast, Relative Average Daily Gain (RADG) was affected by the treatments (P < 0.05). The lyophilized bovine colostrum improved numerically ADG when compared to the piglets fed only with the colostrum from the sow and those fed also shea butter (41g vs 35 and 36 g/d for the first and second groups respectively). A higher RADG was obtained with the piglets from the BCB group (31 ± 1.6 g/d.kg vs 25.3 ± 1.6 g/d.kg and 24.5 ± 1.9 g/d.kg for the SC and SCB groups respectively). Lyophilized bovine colostrum improved RADG, active immunity at weaning and tended to reduce prevalence of diarrhea in newborn piglets.